Strategy Model For Improving Sharia Financing For Empowering UMKM Fostered By PNM In South Labuhan Batu, North Sumatera - Emriana Parapat; Muhammad Syahbudi; Nurwani (LP2M IAIN Palopo, 2024)
One of the sharia products is sharia financing for MSMEs which has been intensified by the community since Covid-19, South Labuhan Batu Regency is one of the areas in North Sumatra whose population is dominated by Islam, the community's willingness to finance based on sharia through PNM Mekaar Syariah is due to the minimal concentration of usury owned by financing through Mekaar Syariah Capital, South Labuhan Batu Regency, in this study using a qualitative research method where data from the study was taken from several sources, namely primary and secondary to support detailed research results, in the study the results of the study were taken through interview techniques with customers, branch managers, deputy branch managers and officers who went into the community, in the results of the study it was found that in implementing their financing, the South Labuhan Batu community often participated in studies that made their understanding of usury very large. The model of the strategy used by PNM Mekaar Syariah to empower MSMEs in the South Labuhan Batu community has several strategies, starting from financing with minimal usury, implementing sponsorship such as providing billboards and banners, providing education and socialization to the community regarding business, monitoring business progress, giving the community time when the business is not running smoothly, and implementing a joint responsibility system for customers who fail to pay. This allows the community to improve and empower their MSMEs and can also provide benefits for PNM Mekaar Syariah itself.